Evaluasi Kepuasan Pasien Terhadap Sistem Pelayanan Kefarmasian Berbasis Syariah di Puskesmas Padang Sari - Asih Puji Lestari; Indah Permata Sari; Fari Rohmi Lutfiani (Indonesian Journal of Medical and Pharmaceutical Science, 2026)
Background: Pharmaceutical services at primary healthcare centers are expected not only to meet quality standards but also to integrate Islamic (sharia-based) values to fulfill the spiritual and ethical needs of Muslim patients. The application of sharia principles such as trustworthiness, clarity of drug information, halal assurance, and ethical service has been shown to enhance patient trust and satisfaction. Methods: This study employed a descriptive observational design with a cross-sectional approach, employing a 15-item structured questionnaire that had been tested for validity and reliability. The collected data were tabulated using Microsoft Excel. Customer satisfaction levels were measured using the five dimensions of the SERVEQUAL measurement system. Results: Patient satisfaction results showed a very satisfactory rating across all SERVQUAL dimensions. Responsiveness scored 97%, reliability 94%, assurance 96%, empathy 95%, and tangible 95%. These findings indicate that pharmaceutical services meet professional standards, are friendly, informative, and equipped with comfortable and well-organized facilities. The majority of respondents were women of productive age, with a high school education. The implementation of Sharia values ​​such as trustworthiness, fairness, and cleanliness supports increased patient comfort and trust. Conclusion: Patient satisfaction with pharmaceutical services at Padang Sari Primary Health Center was categorized as very satisfactory across all SERVQUAL dimensions. These findings reflect high patient satisfaction with service quality and may be interpreted as being consistent with relevant sharia values; however, the implementation of sharia-based pharmaceutical services was not directly measured in this study.